Doses of fluoride toothpaste for children up to 24 months - Henny Sudradjat; Frederic Meyer; Pascal Fandrich; Erik Schulze zur Wiesche; Hardy Limeback; Joachim Enax (Nature Publishing Group, 2024)
Abstract Aim The aim of this study was to test the dose of fluoride toothpaste by parents for their children aged up to 24 months. Methods Parents who use fluoride toothpastes for their children were asked to dose two commercially available toothpastes (A and B) with 1000 ppm fluoride each for their children as they would normally do at home. The toothpaste amounts were weighed, and as reference, the weight of an 'optimal' grain of rice-size amount of each toothpaste was used. Results 61 parents dosed a mean of 0.263 ± 0.172 g toothpaste A and 0.281 ± 0.145 g toothpaste B. The parents' mean doses were 5.9 times higher for toothpaste A and 7.2 times higher for toothpaste B than an 'optimal' grain of rice-size amount (the reference dose as recommended). The difference between parent's and reference dose was statistically significant (p < 0.001). Moreover, 39.3% of parents were not aware about conditions of use and warnings that have to be printed on the package of fluoride toothpastes. Conclusion In this study, parents significantly overdosed the toothpaste for their children. To avoid fluoride intake from toothpaste, parents can choose fluoride-free alternatives for the oral care of their infants and toddlers.